2005
DOI: 10.1254/jphs.fp0040153
|View full text |Cite
|
Sign up to set email alerts
|

The Different Roles of 5-HT2 and 5-HT3 Receptors on Antinociceptive Effect of Paroxetine in Chemical Stimuli in Mice

Abstract: Serotonin (5-HT) is known to be an important mediator in pain modulation. Some centrally acting agents, like selective serotonin reuptake inhibitors (SSRIs), modulate pain. Activation of the endogenous opioid mechanisms or potentiation of analgesic effect by serotonergic and/or noradrenergic pathways might be involved in antinociception of SSRIs. However, peripheral mechanisms of nociception are not clear. In this study, the antinociceptive effect of paroxetine, its interaction with the opioidergic system and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 40 publications
1
23
0
2
Order By: Relevance
“…Newer antidepressants such as those in the SNRI and SSRI classes have been introduced, and their antidepressant function is better understood than that of TCAs. The antinociceptive effects of SSRIs have been reported in a number of animal experiments (12,13,25). One typical SSRI, fluvoxamine, attenuated licking behavior in the late phase of the formalin test (22,30) and also in the hot-plate test (27), but it failed to attenuate mechanical allodynia in a neuropathic pain model (chronic constriction injury model) (9).…”
Section: Time Course and Dose-response Of Paclitaxel-induced Mechanicmentioning
confidence: 99%
“…Newer antidepressants such as those in the SNRI and SSRI classes have been introduced, and their antidepressant function is better understood than that of TCAs. The antinociceptive effects of SSRIs have been reported in a number of animal experiments (12,13,25). One typical SSRI, fluvoxamine, attenuated licking behavior in the late phase of the formalin test (22,30) and also in the hot-plate test (27), but it failed to attenuate mechanical allodynia in a neuropathic pain model (chronic constriction injury model) (9).…”
Section: Time Course and Dose-response Of Paclitaxel-induced Mechanicmentioning
confidence: 99%
“…Paroxetine has a significant antinociceptive effect at 5-20 mg/kg in the hot plate test (Duman et al, 2006) and at 5-30 mg/kg in the writhing test (Ormazabal et al, 2001;Kesim et al, 2005), and an anxiolytic effect at 4-16 mg/kg (Hascoet et al, 2000;Masse et al, 2005). In the present study, imipramine at 3 and 10 mg/kg, milnacipran at 10 mg/kg, and paroxetine at 4 mg/ kg were chosen for chronic administration under a neuropathic pain-like state.…”
Section: )mentioning
confidence: 99%
“…The hot plate test measures the response to a brief, noxious stimulus; the formalin test, on the other hand, measures the response to a long-lasting nociceptive stimulus, and thus, may bear a closer resemblance to clinical pain (Rosland et al, 1990). The hot plate test with its short stimulation properties showed the action on somatic rather than visceral sites (Kesim et al, 2005). Our results showed that administration of olive oil did not raise the pain threshold in comparison with control.…”
Section: Discussionmentioning
confidence: 59%
“…The abdominal-constriction response is thought to involve, in part, local peritoneal receptors (Jais et al, 1997). The chemical stimulus induced by acetic acid provokes continuous and unavoidable pain causing abdominal contractions, movement of whole body, twisting of dorsoabdominal muscles, and a reduction in motor activities, which is evidence of visceral but not somatic pain (Kesim et al, 2005). It is, therefore, possible that the olive oil exerts an analgesic effect probably by inhibiting synthesis or action of prostaglandins.…”
Section: Discussionmentioning
confidence: 99%